Renewable Energy Developments in Indonesia - Muhammad Zulkifli; Ryuji Tohyama; Tomohiro Tohyama; Kazuyuki Maeda (EPI International Journal of Engineering, 2019)
Replacing consumption of fossil fuel with renewable energy is an important way in reducing carbon emission and one of effective solution facing issues of electricity in Indonesia. In light of the perspective of promoting the renewable energy, we plan to use palm oil as biofuels for power generation activities that will help to supply electricity for local community in Indonesia. This paper is a preliminary study that aims to overview the current progress of renewable energy development in Indonesia, also to introducing background of our planning as one of solution in dealing with Indonesia`s current renewable energy usage. Based on expected outputs of our planning, this study attempts to discuss our concept which is to promote of Local Production Energy for Local Consumption and its application which will lead to development of one Smart Energy Community, as one of the key points to developing Smart City.